Research on Vibration Performance of Engine Timing Transmission System with VVT - Jiawang Li; Zhou Lan; Ziming Yin; Tiantian Li (Jixie chuandong)
In order to solve the vibration and reliability problems of timing belt transmission system of a 2.0L VVT engine，the mechanical model of timing drive system is simplified from the point of view of force balance，and the external excitation factors affecting the vibration of timing drive system are quickly found. Through the methods of reducing the fluctuation of camshafts loads，reducing VVT adjusting shock，optimizing belt tensioner internal structure，reducing the vibration of timing belt transmission system and timing tensioner swing，the issues of wear failure of timing tensioner and belt are solved. The key index of the vibration of the timing transmission system is determined，and the reliability test of the engine is verified.